2021
DOI: 10.1002/pro.4188
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of polar interactions in the prion protein triggers misfolding and oligomerization

Abstract: The prion protein (PrP) misfolds and oligomerizes at pH 4 in the presence of physiological salt concentrations. Low pH and salt cause structural perturbations in the monomeric prion protein that lead to misfolding and oligomerization. However, the changes in stability within different regions of the PrP prior to oligomerization are poorly understood. In this study, we have characterized the local stability in PrP at high resolution using amide temperature coefficients (TC) measured by nuclear magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…The view from MD simulations is strongly consistent and synergistic with experiments. Exploiting underexplored chemical shift differences and cycle analyses may provide high-resolution insights for many systems, including a wide variety of proteins and peptide assemblies ( 16 , 21 26 ), and serve as a valuable resource to complement, test, and refine molecular simulations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The view from MD simulations is strongly consistent and synergistic with experiments. Exploiting underexplored chemical shift differences and cycle analyses may provide high-resolution insights for many systems, including a wide variety of proteins and peptide assemblies ( 16 , 21 26 ), and serve as a valuable resource to complement, test, and refine molecular simulations.…”
Section: Resultsmentioning
confidence: 99%
“…However, as the many intra- and intermolecular contributions to chemical shift vary in complex ways with temperature, a quantitative structural interpretation of TCs has remained elusive. Recent studies in our group and others have shown how the complexities of amide temperature dependencies may be simplified by comparing related protein variants, yielding nuanced information on changes in structural stability and sampling of alternative states significant for natural function, disease, drug discovery, and materials ( 6 , 16 26 ).…”
mentioning
confidence: 99%
“…In the case of PUF1, the sequence segments covering β1 (96–144), the α1‐β2 loop, the β2‐α2 loop (168–173), the C‐terminal end of α2 (182–196), the second half of α3 (210–216), and the sequence segment 225–231 are found to have become disordered. An earlier NMR study of the temperature dependence of chemical shifts seen for wt moPrP (Bhate et al., 2021) had indicated that in the absence of added salt, many residues in β1 and the β1‐α1 loop (in sequence segment 96–144), as well as Gln211 in the second half of α3 (in sequence segment 210–216), which is adjacent in structure, sample at least one alternative conformation. Both these sequence segments are disordered in PUF1 suggesting that it is the alternative conformation that is sampled.…”
Section: Discussionmentioning
confidence: 99%
“…segment 225-231 are found to have become disordered. An earlier NMR study of the temperature dependence of chemical shifts seen for wt moPrP(Bhate et al, 2021) had indicated that in the absence of added salt, many residues in β1 and the β1-α1 loop (in sequence segment 96-144), as well as Gln211 in the second half of α3 (in sequence segment 210-216), which is adjacent in structure, sample at least one alternative conformation. Both these sequence segments are disordered in PUF1 suggesting that it is the alternative conformation that is sampled.It is not yet known how the addition of the salt (150 mM NaCl) affects the extents to which the PUFs are populated.…”
mentioning
confidence: 99%
See 1 more Smart Citation